2015
DOI: 10.1007/s11245-015-9319-2
|View full text |Cite
|
Sign up to set email alerts
|

Spin as a Determinable

Abstract: In this paper I aim to answer two questions: 1) Can spin be treated as a determinable? 2) Can a treatment of spin as a determinable be used to understand quantum indeterminacy? In response to the first question I show that the relations among spin number, spin components and spin values cannot be captured by a single determination relation; instead we need to look at spin number and spin value separately. In response to the second question I discuss three ways in which the determinables model might be modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The problems with the DBA can be divided in general problems of the account, and specific problems of its gappy and glutty implementation. In general, one problem is that it is controversial whether quantum observables do in fact have a determinable‐determinate structure—Wolff (2015). Furthermore, the DBA explicit commitment to the non‐reducibility of determinables in terms of logical construction of determinates may be found problematic—Torza (2020).…”
Section: Accounts Of Qimentioning
confidence: 99%
“…The problems with the DBA can be divided in general problems of the account, and specific problems of its gappy and glutty implementation. In general, one problem is that it is controversial whether quantum observables do in fact have a determinable‐determinate structure—Wolff (2015). Furthermore, the DBA explicit commitment to the non‐reducibility of determinables in terms of logical construction of determinates may be found problematic—Torza (2020).…”
Section: Accounts Of Qimentioning
confidence: 99%
“…In the recent debate, the most discussed of these cases is indeterminacy in quantum mechanics (QM). Many have shown that a crucial feature of QM is that we cannot always ascribe definite properties to microscopic systems, and have taken this as an instance of MI (Bokulich, 2014; Calosi & Wilson, 2018; Darby, 2010; Skow, 2010; Wolff, 2015; inter alia ).…”
Section: Getting Rid Of Quantum Indeterminacy?mentioning
confidence: 99%
“…For instance, in the paper I already mentioned Glick (2017) does not discuss the meta‐level approach, and focuses his attention on the account defended by Calosi and Wilson (2018), which builds upon Wilson's (2013) object‐level approach. The main reason for the restriction is that it has been shown in various ways that the meta‐level approach to MI is ill suited to treat quantum indeterminacy (Bokulich, 2014; Calosi & Wilson, 2018; Darby, 2010; Skow, 2010; Wolff, 2015).…”
Section: Metaphysical Indeterminacy Needs Not Be Fundamentalmentioning
confidence: 99%
“…The DBA was first proposed in Wilson (2013), and defended in Wilson (2017). It has been applied to several cases: 22 indeterminate boundaries (Wilson 2013(Wilson , 2017, the open future (Wilson 2017;Mariani and Torrengo 2020), fundamentality (Mariani and Torrengo 2020), and quantum indeterminacy (Bokulich 2014;Wolff 2015;Lewis 2016, Calosi andWilson (2018, Forthcoming), Wilson (2020), Calosi and Mariani (Forthcoming a, b)). Wilson herself suggests two different characterization of the DBA.…”
Section: The Determinable Based Account Of Metaphysical Indeterminacymentioning
confidence: 99%